(untitled) (Medicine Today, 2025)
Introduction with Objective: The aim of the present study was to assess the association of serum leptin level with preeclampsia. Materials and Methods: This cross-sectional study was conducted from March 2022 to February 2023 in the department of Laboratory Medicine, Fetomaternal Medicine and Obstetrics and Gynaecology, BSMMU. A total 80 cases were selected as study population as per inclusion and exclusion criteria. They were grouped as preeclamtic (group I) and normal pregnant women of more than 20 weeks of gestation (group II). After taking written informed consent, 2.0 ml of random venous blood and 24 hours urine for protein were collected. Serum leptin level was estimated in Laboratory Medicine department and 24 hours urinary protein measured in Biochemistry and Molecular Biology department. After data collection and processing, all statistical analysis were done by SPSS software windows version 26. Result: The mean serum leptin level was found 28.3±12.52 ng/ml in group I and 14.24±5.10 ng/ml in group II. The difference was statistically significant (p 0.001) between two groups in unpaired t-test. Mean 24 hours urinary protein was 0.33±0.03 gm and 0.12±0.13 gm in group I and II respectively and the difference was statistically significant (p in unpaired t-test. There was positive linear relationship between 24 hours urinary protein and serum leptin level (r=+0.225, p>0.05) found in Pearson’s correlation co efficient test. In ROC curve analysis, cut off value of serum leptin was found 21 ng/ml with 80% sensitivity and 90% specificity. The area under curve (AUC) of serum leptin level was 0.904. In our study, 32 preeclampsia patients (80%) had serum leptin level was ≥21 ng/ml which considered positive This finding of the study revealed that increased serum leptin level was associated with preeclampsia. Conclusion: Serum leptin level was increased in preeclamptic study group compared to normal pregnancy. Serum leptin level may be used as a biomarker of preeclampsia to help the clinicians for diagnosis. Medicine Today 2025, Vol.37 (2): 160-163